Pendidikan Inklusif dalam Pandangan Islam (Studi Kasus di SMK Negeri 8 Surakarta Tahun Pelajaran 2016/2017) - Subekti, Ika, Drs. Saifuddin Zuhri, M.Ag (2017)
The inclusive education is a kind of education that receives many different students' characters and backgrounds to learn together within a learning atmosphere. In the perspective of Islam, education is an obligation either to understand Islam or to develop culture or civilization. The problem which can be formulated from the main problem which becomes object of the study for this research is how inclusive education in Islamic's view is applied at SMK Negeri 8 Surakarta? The objective of the study is to describe the inclusive education in Islamic's view at SMK Negeri 8 Surakarta. The benefit of this study is expected to add knowledge and researcher's point of view on inclusive education in the view of Islam in SMK Negeri 8 Surakarta. This research includes qualitative descriptive research. The subject of this study is the child with special needs in SMK Negeri 8 Surakarta. Data collection is the process of data search used by observation, interview, and documentation. Data, then, analyzed by interactive method to make a conclusion. The result of the study shows that inclusive education inculcates early social education to learners both children with special and non-special needs children, so through inclusive education, children respect with each other for differences and eliminate discriminatory attitude. The view of Islam according Qur'an and Hadith stresses the importance of education without distinguishing humans. Inclusive education in SMK Negeri 8 Surakarta has advantages and disadvantages. The development of inclusive education that happens at SMK Negeri 8 Surakarta, are that: since early childhood the students have a better understanding of differences and diversity, the emergence of empathy in students naturally, a culture of mutual respect among students, reducing the occurrence of labeling to all children (particularly on children with special needs and the disabled), the emergence of cooperative and collaborative culture at learners, thus allowing the mutual help between one another, raise of self-confidence through acceptance and engagement in the classroom, developing tolerance, and facilitating social interaction between friends.